Antihypertensive Treatment and Central Arterial Hemodynamics: A Meta-Analysis of Randomized Controlled Trials - Cheng, Yi-Bang; Xia, Jia-Hui; Li, Yan; Wang, Ji-Guang (Frontiers in Physiology, 2021)
Background: Antihypertensive treatment may have different effects on central arterial hemodynamics. To what extent the difference in effects differ between various antihypertensive drugs remains undefined. Methods: We conducted a systematic review and meta-analysis of randomized controlled trials that explored effects of antihypertensive agents on both central and peripheral systolic blood pressure and pulse pressure or on central augmentation index, with a special focus on comparisons between newer (renin-angiotensin-aldosterone system inhibitors and calcium channel blockers) and older antihypertensive agents (diuretics and β- and α-blockers). Results: In total, 20 studies (n=2498) were included. Compared with diuretics (10 studies), β-blockers (16 studies) or an α blocker (1 study), renin-angiotensin-aldosterone system inhibitors (21 studies) and calcium-channel blockers (6 studies) more efficaciously reduced both central and peripheral systolic blood pressure by a weighted mean difference of -5.63 mm Hg ( 6.50 to -4.76 mm Hg) and -1.97 mm Hg (-2.99 to -0.95 mm Hg), respectively. Compared with older agents, the newer agents also more efficaciously reduced central pulse pressure ( 3.27 mm Hg; -4.95 to -1.59 mm Hg), augmentation index (-6.11%; 7.94 to 4.29) and augmentation, but not peripheral pulse pressure (P≥0.053). Accordingly, the newer agents reduced central-to-peripheral pulse pressure amplification significantly less than the older agents (0.11 mm Hg; 0.05 to 0.17 mm Hg). Conclusions: Newer agents such as renin-angiotensin-aldosterone system inhibitors and calcium-channel blockers were significantly more efficacious than older agents in their effects on central hemodynamics.